Identity Based Distributed Provable Data Possession in Multi Cloud Storage - Abinaya, A; Fathima Bibi, K (International Journal of Computer Sciences and Engineering, 2025)
Online data integrity checking is very main in cloud storage space. It can make the users verify whether their outsourced data is kept intact without downloading the whole data. In some application scenarios, the clients have to store their data on multi-cloud servers. At the same time, the integrity examination protocol must be efficient in order to save the verify cost. Thus a novel remote data integrity checking model: identity-based distributed provable data possession (ID-DPDP) is proposed for a multi-cloud storage. Based on the bilinear pairing, a concrete ID-DPDP protocol is design. The current paper proposed ID-DPDP protocol is provably protected under the hardness assumption of the standard computational diffie-hellman (CDH) problem. In addition to the structural to the advantages of elimination of certificate management, the ID-DPDP protocol is efficient and flexible. Based on the user authorization, the proposed ID-DPDP protocols perform private verification, delegated verification, and public verification.